Study on Catalytic Ozone Oxidation with Nano-TiO2 Modified Membrane for Treatment of Municipal Wastewater - Zhu, Yueqi; Zhang, Hongwei; Zhang, Xuehua (Asian Journal of Chemistry, 2014)
This study reports the application of nano-TiO2 modified membrane technology in municipal wastewater treatment. Ozone aeration can produce a large numbers of high oxidizing free radicals (hydroxyl radical HO·) to degrade organic matters when ozone contacts with nano-TiO2 modified membrane. This is called catalytic ozone oxidation process. This approach is a new frontier of municipal wastewater treatment, which has excellent reactive activity and degradation of organic compounds without the need for catalyst recycling. Our purpose is to remove organic matters by ozone aeration pre-treatment and nano-TiO2 modified membrane. In this study, municipal sewage is raw water, polyvinylidene fluoride (PVDF) and the nano-TiO2 modified polyvinylidene fluoride ultra-filtration membranes are experimental materials. Results suggest that new method (TiO2 + O3) removal rate of organic matters is 66.4 %, which is 13.3 % higher than original membrane with O3 (PVDF + O3) under the same condition. Compared with traditional polyvinylidene fluoride membrane filtration whose removal rate is 38.7 %, this novel approach is 27.7 % higher.